Pengaruh Faktor Pengembangan Sumber Daya Manusia terhadap Komitmen dan Kinerja pada Manajer Proyek Konstruksi - Sahadi, Sahadi; Wibowo, M. Agung (Department of Civil Engineering, Diponegoro University, 2013)
This study aims to find out the influence of human resources development factor on the performance of construction managers through their commitment using the structural equation modeling (SEM) approach. The results of study indicate that leadership, organization climate, organization culture, communication climate, trust, work motivation, work experience, reward/salary, and work satisfaction have a positive influence on the commitment and performance of construction project manager and the commitment also has a positive influence on these managers. Among the variables that have dominant influence on the commitment and performance of construction project managers is the reward, in the sequence where work satisfaction and leadership influence the commitment, which in turn influence the reward, and finally, commitment and work experience work in tandem to influence the performance.